2013
DOI: 10.1146/annurev-pathol-020712-164014
|View full text |Cite
|
Sign up to set email alerts
|

The Immunobiology and Pathophysiology of Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune disease characterized by clinical homogeneity among patients, an overwhelming female predominance, production of a multilineage immune response to mitochondrial autoantigens, inflammation of small bile ducts, and in some patients the development of fibrosis and cirrhosis. The targets in this disease are small bile ducts, and the prototypic serologic response includes antimitochondrial antibodies (AMAs). Several key observations have greatly advanced our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
263
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(277 citation statements)
references
References 153 publications
7
263
0
7
Order By: Relevance
“…Somatic hypermutation of the V region will occur simultaneously, resulting in affinity maturation. As observed in this study, the highly expanded and expressed clones, which also resulted in the significantly biased usage of IGHV segments in PBC patients and its subgroups, could be due to the consequence of ongoing stimulation by endogenous bile duct epithelial Ags (1,19,20). The effective treatment of PBC patients who were refractory to UDCA with rituximab, which led to B cell depletion, through the reduction of AMA-secreting B cells, the titer of AMAs and serum IgM/G/A level, as well as serum ALP level, suggests that the highly expanded and expressed B lymphocytic clones have contributed to the abnormality of peripheral B cell immunity and may be involved in the pathogenesis of PBC patients (28).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Somatic hypermutation of the V region will occur simultaneously, resulting in affinity maturation. As observed in this study, the highly expanded and expressed clones, which also resulted in the significantly biased usage of IGHV segments in PBC patients and its subgroups, could be due to the consequence of ongoing stimulation by endogenous bile duct epithelial Ags (1,19,20). The effective treatment of PBC patients who were refractory to UDCA with rituximab, which led to B cell depletion, through the reduction of AMA-secreting B cells, the titer of AMAs and serum IgM/G/A level, as well as serum ALP level, suggests that the highly expanded and expressed B lymphocytic clones have contributed to the abnormality of peripheral B cell immunity and may be involved in the pathogenesis of PBC patients (28).…”
Section: Discussionsupporting
confidence: 51%
“…A high level of serum IgM in most PBC patients is a unique phenomenon. Studies suggested it might be a consequence of hyperactive innate immunity independent of T cells and mediated by IgM memory B cells either in the bloodstream or in the spleen (1,5,29,30). Elevated serum IgM level has been used as a diagnostic marker for PBC, and the reduction of serum IgM level has been used as a marker of disease alleviation by clinicians (28,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As important immune cells, CD4+ T cells are involved in the pathogenesis of PBC (Hirschfield and Gershwin 2013;Wang et al 2015a;Webb et al 2015). One paper reported that the concentration of Th1-related IFN-γ was increased in PBC patients but decreased after UDCA treatment, indicating the relationship of this cytokine with disease activity (Saeki et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The typical characteristic of the disease is the presence of antimitochondrial autoantibodies (AMA), which are present in high amounts. The autoantigens to which the immune responese is directed in PBC has been identified as the E2 subunits of the 2-oxo-acid dehydrogenase complexes (2OADC-E2), including the E2 subunits of the pyruvate dehydrogenase complex (PDC-E2), branched chain 2-oxo acid dehydrogenase complex (BCOADC-E2), and 2-oxoglutarate dehydrogenase complex (OGDC-E2) (5). The immunodominant autoantigen within this group is PDC-E2 (6; 7).…”
Section: Introductionmentioning
confidence: 99%